Evaluation of Attitudes and Behaviors of Families with Children Aged 0-24 Months about Childhood Vaccines - Sümeyye Evsile; Gökçe Celep; Ada Perin Duran; Ali Bahadır; Kader Memiş; Muhammed Davvara; Nurgül Kılıç; Sema Çayır; Senanur Akıncı (Güncel Pediatri)
Introduction: The aim of this study was to evaluate the knowledge and attitudes of parents with children aged 0-24 months about childhood vaccines. Materials and Methods: In this cross-sectional and descriptive study, 408 parents with children aged 0-24 months who applied to the General Paediatrics Polyclinics of Sabuncuoğlu Şerefeddin Training and Research Hospital in April and May 2024 for examination or control purposes and who agreed to participate in the survey study were included. The questionnaires were conducted by face-to-face interviews with the parents and the information obtained was recorded on a questionnaire form consisting of 22 questions in total. SPSS package programme was used for data analysis and p<0.05 was accepted as significant. Results: It was observed that 43% (n=179) were boys, 56.1% (n=229) were girls and the mean age was 12 months. When the distribution of the surveyed parents was analysed, it was seen that 73.3% were mothers. While the rate of complete vaccination among all participants was 88%, 85% of the parents thought that vaccines were necessary. The rate of parents who were against vaccination was found to be 4%. While the rate of knowing the vaccines not included in the Ministry of Health vaccination calendar (Rota virus, Influenza, Meningococcus and Human papilloma virus) was 57.6%, the rate of vaccination was 31.9%. A statistically significant relationship was found between the knowledge of non-routine vaccines and both the educational level and financial income status of the parents (p<0.05). Conclusion: Income and education levels of parents were found to be important in the administration of non-routine vaccines, and we think that they should be included in the routine vaccination schedule considering the severity of the diseases. It was determined that vaccine refusal is an increasing problem in our country as in the whole world. Despite all these, the fact that parents prefer healthcare professionals as a source of information shows that healthcare professionals are an effective factor on vaccination rates.